Comparative efficacy, safety, and cost of iron chelation monotherapy vs. combination therapy in pediatric beta-thalassemia major: a single-center retrospective study - Dewi Sharon Simorangkir; Nafrialdi Nafrialdi; Pustika Amalia Wahidiyat; Vivian Soetikno (Paediatrica Indonesiana, 2022)
Background Iron chelation therapy is used to maintain iron balance in β-thalassemia major patients who undergo repeated blood transfusions. Objective To compare the efficacy, safety, and cost of iron chelation combination regimens [deferiprone (DFP) + deferoxamine (DFO) or DFP + deferasirox (DFX])] vs. high-dose DFP monotherapy (≥ 90 mg/kg/day) in pediatric β-thalassemia major patients. Methods This cross-sectional, retrospective study was done at Cipto Mangunkusumo Hospital, Jakarta, Indonesia. Retrospective data was obtained from electronic medical records of pediatric b-thalassemia major patients with serum ferritin of ≥ 2,500 ng/mL and/or transferrin saturation of ≥ 60%, who received either combination or monotherapy iron chelation agents. Outcome effectiveness was determined by the reduction of serum ferritin level of at least 80%. Safety was analyzed descriptively. A pharmacoeconomic analysis was performed based on clinical outcomes consisting of effectiveness and direct medical costs. Results At the end of the study, serum ferritin was reduced in 34.7% of the combination therapy group and 27.5% of the monotherapy group, however there was no significant difference between the two treatments (P=0.391). Nine (19.5%) patients on combination therapy and 17 (21.2%) patients on monotherapy had adverse drug reaction (ADR), with the most frequently reported ADR was elevated transaminase enzyme levels. Cost minimization analysis revealed that monotherapy for 6 months was IDR 13,556,592.64 less expensive than combination therapy (IDR 44,498,732.07); whereas monotherapy for 12 months was IDR 20,162,836.10 less expensive than combination therapy (IDR 78,877,661.12). Conclusion Combination regimens are as effective as monotherapy regimens in reducing serum ferritin in pediatric β-thalassemia major patients. There is no differences of ADR between combination or monotherapy. The average cost per patient is less expensive with monotherapy compared to combination therapy.